La desnutrición y la inflamación—"quemar la casa": La inflamación como una respuesta fisiológica adaptiva o autodestrucción - Jensen, Gordon L. (Acta Médica, 2016)
A summary of my 2014 Rhoads Lecture is presented that explores our progress in understanding the complex interplay of malnutrition and inflammation. A historical perspective is provided that highlights the contributions of some of the key pioneers in the nutrition assessment field. Advances in agriculture, education, public health, healthcare, and living standards have affected traditional settings for malnutrition. The chronic disease, surgery, and injury conditions that are associated with modern healthcare are becoming prevalent settings for malnutrition. One consequence has been a growing appreciation for the contributions of inflammation to malnutrition in these clinical conditions. This recognition has driven a fresh look at how we define and think about malnutrition syndromes. An inflammatory component is included in the definitions suggested by the recent Academy of Nutrition and Dietetics and American Society for Parenteral and Enteral Nutrition consensus report that also describes characteristics recommended for the identification and documentation of malnutrition. Efforts are currently underway to evaluate the feasibility and validity of this approach. Recent advances in research highlight the profound impact of inflammation-mediated erosion of muscle mass on clinical outcomes. Research to identify better biomarkers of inflammation and malnutrition must be a leading priority. New “omics” approaches are an especially promising avenue of biomarker investigation. Inflammation can be a good thing; let’s try to keep it that way. (JPEN J Parenter Enteral Nutr. 2015;39:56-62)